Chronic obstructive pulmonary disease and comorbidities' influence on mortality in non-small cell lung cancer patients. (3rd August 2019) - Media, Ara Shwan; Persson, Martin; Tajhizi, Navid; Weinreich, Ulla Møller
Abstract: Background : In Denmark, lung cancer is the most common cause of cancer-related death and chronic obstructive pulmonary disease (COPD) is the most common comorbidity in patients with non-small cell lung cancer (NSCLC). The aim of this study was to investigate the influence of COPD and other common comorbidities on NSCLC mortality. Methods : Patients ( n = 534) diagnosed with NSCLC at Aalborg University Hospital from 2008–2010 were included retrospectively in this study. Patient records were assessed and the population was dichotomized in COPD and non-COPD subgroups. Comorbidities i.e., ischemic heart disease, hypertension, diabetes mellitus, apoplexia, former malignancy, interstitial lung disease and psychiatric comorbidity were registered and a comorbidity count were calculated. Survival was assessed with log-rank test and uni- and multivariate regression analysis were performed for COPD-status and comorbidity count adjusting for age, gender, BMI, smoking exposure, cancer stage, method of treatment and eastern cooperative cancer group (ECOG) performance status score. Results : Of 534 NSCLC patients included, 470 were divided into COPD and non-COPD subgroups, 70% with COPD (329/470) and 30% without COPD (141/470). Only 32.5% of the patients in the COPD-group had previously diagnosed COPD. Log-rank test did not show statistically significant difference in survival between the COPD and non-COPD groups ( p = .215). Multivariate Cox regression analysis did not show statistically significant association between overall 5-year mortality and the presence of COPD (HR-adj = 0.808, 95% CI = 0.612; 1.068) or other comorbidities (HR-adj = 1.101, 95% CI = 0.979; 1.237) when adjusted for age, BMI, gender, smoking exposure, ECOG performance status, treatment and TNM-stage. Conclusion : Our findings do not suggest that COPD nor other common comorbidities are significantly associated with higher mortality in NSCLC patients.